Crabs infected with Paragonimus metacercariae from Condebamba Valley (Cajamarca) - Tantaleán V., Manuel (1974)
In Condebamba Valley (Cajamarca) between February and July 1973; 69 crabs Pseudothelphusa chilensis were collected, of them (34 males and 35 females) 22 (64.7%) males and 29 (28.85%) females were infected with metacercariae, this results are consistent with Cuba et al. (1974) report.